Flat-Top Metasurface Broadband Mushroom Antenna for Microwave Power Transmission - Haixuan Li; Rui Zhang; Bingchuan Xie; Lu Tian; Zhicheng Wang; Zhengyu Deng (IEEE Access)
In this paper, a flat-top metasurface broadband mushroom antenna for microwave power transmission (MPT) is proposed. It has a $4× 4$ array of patches that are connected to the ground through vias to form a mushroom structure to reduce back lobe radiation. The antenna is fed by a microstrip, with the feeding slot located just underneath the central gap between the mushroom cells. This configuration enables the simultaneous excitation of dual resonance modes, resulting in aperture radiation and a wide impedance bandwidth. The final design has an overall dimension of $1.96λ _{0} × 1.96λ _{0} × 0.09λ _{0}$ at 5.4 GHz. After simulation and measurement, The final impedance bandwidth is 4.2-7.0GHz (50%), the flat-top bandwidth is 4.2-6.3GHz (40%), the peak gain is 8.4dBi, and the stable 1dB flat-top beam bandwidths of the E-plane and H-plane from 4.2GHz to 5.4GHz are both greater than 67° and 38°, and the 3dB flat-top beam bandwidths of the E-plane and H-plane are both stably greater than 85° and 24° at 5.6-6.3GHz. The stable flat-top radiation pattern makes it more popular in microwave radio transmission. Compared with other works, this antenna has the advantages of broadband, compactness, and wide beamwidth.